The Issue of Inner Speech Mechanisms in the Nikolay Zhinkin’s Psycholinguistic Legacy - Nurtayeva, Yulia (East European Journal of Psycholinguistics, 2014)
The article analyzes the works of a well-known national psycholinguist N. Zhynkin, which covers the development of inner speech of a human, its originality as a kind of speech activity and the issue of code conversion unit. The concept of inner speech and its mechanisms is a major issue in the development of speaking. The correlation between thought and language as a means to achieving speech activity was examined in details for the first time by N. Zhynkin. In his theory, he uses “code” as a basis, considering that the code can be called a system of symbolic notation. From this standpoint, language is viewed as a code and a system of material signals, in which language can be implemented (visible, tangible signals). According to N. Zhynkin, inner speech is a set of standard grammar rules and even the alphabet of vocabulary. Thus, the inner speech is a language which manages, regulates not only silent movements of the body, but also monitors any communication. References Zhinkin, N. (1982). Rech kak provodnik informatsii [Speech as a conduit for information] Moscow: Nauka. Zhinkin, N. (1958). Mehanizmyi rechi [Mechanisms of speech]. Moscow: APN RSFSR. Zhinkin, N. (1964). O kodovyih perehodah vo vnutrenney rechi [On code transitions in inner speech]. Problemy Linguistiki, 6, 26 – 38. Zhinkin, N. (1998). Yazyik. Rech. Tvorchestvo [Language. Speech. Creativity] Moscow: Maze. Kovshikov, V., Gluhov, V. (2007). Psiholingvistika. Teoriya rechevoy deyatelnosti [Theory of speech activity] Moscow: Astrel. Kalmykova, L.(2008) Psihologiya formuvannya movlennevoyi diyalnosti u ditey doshkilnogo viku [Psychology formation speech activity in children of preschool age]. Kyiv: Feniks.